Population Frequencies for CSF1PO, TPOX, TH01, F13A01, FES/FPS y VWA in Seven Amerindian Populations from Colombia (2022)
eng: While previous research has examined the STR variability among Caucasian and Afro-Colombian populations, few studies have focused on the STR variability among Amerindian tribes. In Colombia, Amerindians make up approximately 1.7 percent of the population and they are located primarily in the Amazonian/Orinoquian region, the Northeast, Southwest, and Pacific regions of the country. The F13A01, FES/FPS, VWA, CSF1PO, TPOX, and THO1 STR loci were amplified from DNA obtained from 7 Amerindian populations named Cubeo (N=49), Curripaco (N=32), Desano (N=28), Tucano (N=26), Embera (N=31), Puinabe (N=77), and Nukak (N=29). Under examination were the allele frequencies and other forensically important parameters. The data provide little evidence of deviation from independence within the populations studied. The complete dataset is available to any researcher via electronic mail from the corresponding author.